Influence of Communication Channel and Information Form on Consumers' Purchase Behaviour - Yong Wang; Xue Gu; Zheng Cui; Yang Li (Tehnički Vjesnik, 2022)
Along with the popularity of the omni-channel strategy and new communication technology, companies can communicate with consumers using different forms of information (listed or narrative), both online and offline. However, the effectiveness and mechanism of information forms on consumer behaviour remain unclear. This study investigates the different effects of information forms on consumers' purchase behaviour, both online and offline. Two surveys and four laboratory experiments were conducted to investigate whether and why consumers would react differently to information forms within different communication channels. The empirical results indicated that, for highly involved consumers, online listed information was more effective than narrative information, while the opposite was true in offline situations. However, for consumers with low involvement, listed information was more effective than narrative information both online and offline. The results showed that the influence of information forms was mediated by consumers' perceived information quality. Our findings extend the current understanding of how information affects consumers' behaviours and provide practical suggestions for marketers' omni-channel operations.